Analisis Pengakuan Pendapatan Pada PT. PLN (Persero) ULP Muncar Banyuwangi - Revi Almaningrum Herti; Febriyanti Latifatul Azizah; Munir Is’adi (PT. Padang Tekno Corp, 2025)
Maximizing profits is the main goal of a company, and revenue is one of its components. Regarding the main idea of ​​the issue, namely the measurement and recognition of income. PSAK No. Income 23 is covered in the Statement of Financial Accounting Standards. This research aims to determine whether the income of PLN (Persero) ULP Muncar Banyuwangi is recognized and measured in accordance with the requirements of PSAK No.23. Descriptive analysis is the technique used. PLN (Persero) ULP Muncar Banyuwangi provided the primary and secondary data used. Based on research findings, it can be said that the company’s income comes from operational and non-operational sources, and principles related to revenue recognition and measurement have been used. According to PSAK No. 23, corporations record non-performing loans using the cash basis, use the accrual basis in revenue recognition, and measure income at fair value.